Challenge Based Learning and Lean Startup methodologies use for developing technical and social skills: Una experiencia de aplicación en el Grado en ingeniería agraria - Campelo Rodríguez, María Piedad; Robles Robles, Rita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Degree of Agricultural Engineering from the University of León (Spain) qualifies for Technical Agricultural Engineer profession. To this end, technical (hard) skills -some of them in economics and business- and social (soft) skills need to be developed. Both Challenge Based Learning and Lean Startup were implemented in the subjectof Principles of Economics and Agricultural Businesses Administration in order toimprove the acquisition of these competences. The methodological approach highlysatisfied the students who presented nine prototypes offering solutions based ondigitalization, e-commerce, bioeconomy, sustainability and the environment. Theimprovement of the entrepreneurial intention of the students was also verified.